Meta-Analysis Study: Positive Psychotherapy To Lower Depression Levels - Luh Ade Putri Andayani (Ridwan Institute, 2021)
This study aims to determine the effectiveness of positive psychotherapy to reduce the level of depression by using a meta-analysis method through a literature review – 14 international research journals related to research variables. Based on the processing of M, SD, and N data, it was found that the effect size values obtained from random effects were 0.10 (95% CI = -0.691597 to 0.89557, P = 0.08) and I2 (inconsistency) of 93.8% (95% CI = 91.6% to 95.1%) . This means that giving positive psychotherapy has a small and insignificant effect on reducing depression levels and there is publication bias.